2010
DOI: 10.1177/1934578x1000500834
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Activity and Chemical Composition of Essential Oils from Aromatic Plants of Central West Argentina

Abstract: The essential oils of seven aromatic plants from central west argentina were isolated by steam distillation and analyzed by a gas chromatography mass spectrometry technique. The oils were screened for cytotoxicity and In Vitro inhibitory activity against herpes simplex virus type 1 (HSV-1), dengue virus type 2 (DENV-2) and Junin virus (JUNV). The oils showed a variable virucidal action according to the virus. JUNV was the least susceptible virus in comparison with HSV-1 and DENV-2. The better relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…While the antimicrobial properties of plant based essential oils have been examined in detail against bacteria (Didry et al 1994;Friedman et al 2002;Knowles et al 2005;Peñalver et al 2005;Callaway et al 2008;Ravishankar et al 2009Ravishankar et al , 2010Reichling et al 2009), they have only recently been examined for their antiviral properties. The majority of this work has been directed towards enveloped viruses of clinical importance (Reichling et al 2005(Reichling et al , 2009Koch et al 2008;Loizzo et al 2008;Meneses et al 2009;Garcia et al 2010;Jackwood et al 2010;Ocazionez et al 2010;Wu et al 2010;Garozzo et al 2011). Limited research has looked at the efficacy of essential oils against nonenveloped viruses.…”
Section: Discussionmentioning
confidence: 99%
“…While the antimicrobial properties of plant based essential oils have been examined in detail against bacteria (Didry et al 1994;Friedman et al 2002;Knowles et al 2005;Peñalver et al 2005;Callaway et al 2008;Ravishankar et al 2009Ravishankar et al , 2010Reichling et al 2009), they have only recently been examined for their antiviral properties. The majority of this work has been directed towards enveloped viruses of clinical importance (Reichling et al 2005(Reichling et al , 2009Koch et al 2008;Loizzo et al 2008;Meneses et al 2009;Garcia et al 2010;Jackwood et al 2010;Ocazionez et al 2010;Wu et al 2010;Garozzo et al 2011). Limited research has looked at the efficacy of essential oils against nonenveloped viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antimicrobial properties of essential oils have been widely recognized [3,4,5,6] thanks to several studies which showed a synergistic effect of several components of essential oils against various human pathogens [1]. Essential oils have been used since ancient times, in folk medicine throughout the world, to preserve a good health status [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of such antiviral research has been directed toward clinically relevant enveloped viruses (30,39,47,51,54,55,56,57,58,59,60,61,62), such as herpes simplex virus 1 (HSV-1) (48,52,53) and influenza A virus (46,49,50), with only limited work performed using nonenveloped viruses such as NoV. A few studies have compared the antiviral efficacies of plant antimicrobials with both enveloped and nonenveloped viruses. The observed antiviral effect has usually been greater for enveloped viruses.…”
mentioning
confidence: 99%